2010
DOI: 10.3390/ma3073867
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Glass and Glass-Ceramic Scaffolds for Bone Tissue Engineering

Abstract: Traditionally, bioactive glasses have been used to fill and restore bone defects. More recently, this category of biomaterials has become an emerging research field for bone tissue engineering applications. Here, we review and discuss current knowledge on porous bone tissue engineering scaffolds on the basis of melt-derived bioactive silicate glass compositions and relevant composite structures. Starting with an excerpt on the history of bioactive glasses, as well as on fundamental requirements for bone tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
642
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 934 publications
(695 citation statements)
references
References 225 publications
15
642
2
4
Order By: Relevance
“…After soaking in SBF, Ca 2+ ions were readily to release from the scaffolds and an increase of pH value occurred due to the production of OH − induced from the hydrolysis of Ca 2+ accompanied with the degradation of scaffolds [51]. However, β-Ca 2 SiO 4 scaffolds sintered at 1200 °C were favorable to achieve a more balanced pH value in the microenvironment owing to the highest crystallinity.…”
Section: Discussionmentioning
confidence: 99%
“…After soaking in SBF, Ca 2+ ions were readily to release from the scaffolds and an increase of pH value occurred due to the production of OH − induced from the hydrolysis of Ca 2+ accompanied with the degradation of scaffolds [51]. However, β-Ca 2 SiO 4 scaffolds sintered at 1200 °C were favorable to achieve a more balanced pH value in the microenvironment owing to the highest crystallinity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that various bone grafting materials, successfully used in clinic, have a high angiogenic potential. For instance, various in vitro studies showed increased VEGF and fibroblast growth factor (FGF-2) secretion by fibroblasts, after direct and indirect contact with 45S5 Bioglass ® particles, which was associated with increased endothelial cell proliferation and formation of a tubular network [9][10][11][12] . A clinical study demonstrated increased angiogenesis following the application of a nanocrystalline hydroxyapatite paste in post-extractive sockets 13) .…”
Section: Introductionmentioning
confidence: 99%
“…The first commercially available bioactive glass, known as ''45S5'', has shown positive interaction with both hard and soft tissues [7]. However, the lack of versatility in material processing and inherent brittleness of bioactive glasses limits their applicability in load bearing applications [8,9]. Previous research postulates that polymer/bioglass composite materials could combine the osteoconductive properties, stiffness and strength of bioactive glasses with the processability of biodegradable polymers in order to increase the applicability of glass-based materials for tissue augmentation [10,11].…”
Section: Introductionmentioning
confidence: 99%